The influence of adverse childhood experiences (ACEs) on the self-control of recidivists of the women’s correctional institution - Putri Nurhaliza; Gladis Corinna Marsha; Aziza Fitriah (Jurnal Psikologi Tabularasa, 2025)
A recidivist is an individual who reoffends after serving a previous sentence, which is often associated with low Self-Control. Low Self-Control can be influenced by traumatic childhood experiences, also known as Adverse Childhood Experiences (ACEs). This study aimed to analyze the effect of ACEs on the Self-Control of recidivists in women’s correctional institutions. The research used a quantitative correlational design. The study population consisted of 549 inmates, and the sample comprised 107 female recidivists selected through purposive sampling. The research instruments were the WHO ACE-IQ and the Indonesian-adapted Brief Self-Control Scale (BSCS). Data were analyzed using simple linear regression with JASP 0.19.3 software. The results showed that ACEs had a significant negative effect on Self-Control, explaining 8.7% of its variance (p < 0.01). These findings highlight the importance of trauma-based psychological rehabilitation to improve Self Control and help prevent recidivism in women’s correctional institutions.